Method for increasing compression resistance of geopolymer based on urease induced calcium carbonate precipitation
Calcium carbonate precipitation technology is used to deposit calcium carbonate in fly ash base polymers, which solves the problems of low efficiency and complex operation improvement of compressive performance of local polymers in the prior art, and achieves efficient and environmentally friendly compressive performance improvement and waste resource reuse.
Patent Information
- Application Number
- CN202411926891.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The prior art has problems of inefficiency, high cost and complex operation in improving the compressive performance of ground polymers. In particular, microbial induced calcium carbonate precipitation technology requires precisely controlled culture environment and long-term reaction cycles, resulting in low efficiency.
Urease-induced calcium carbonate precipitation technology is used to catalyze urea hydrolysis to form calcium carbonate precipitation through urease, which is directly deposited in the fly ash base polymer to form a stable composite structure and improve compressive resistance. This method is simple to operate, low cost and wide application.
It significantly improves the compressive resistance of the fly ash base polymer, realizes the reuse of waste resources, has low energy consumption and low carbon dioxide emissions, meets the requirements of green and environmental protection, and reduces the complexity of the process flow.
Smart Images

Figure CN119735394A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of civil engineering or building materials, and in particular to a method for increasing the compressive properties of geopolymers based on urease-induced calcium carbonate precipitation. Background Art
[0002] Geopolymer (GP) is a new type of green gel material, developed and named by French scientist Joseph Davidovits in 1978. It refers to an inorganic gelling material that can generate a three-dimensional network structure with -Si-O-Al-O- as the basic structural unit by using natural minerals or solid waste under the action of acid or alkaline activators. The material sources are wide and cheap, such as kaolin, fly ash, blast furnace slag, rice husk ash, zeolite, clay, etc. Among them, the material with fly ash as the main raw material, which is polymerized by alkaline activators to generate a three-dimensional cross-linked structure, has the characteristics of wide raw material sources, low price and environmental friendliness. Therefore, fly ash-based polymer materials have become an important green building material, especially in structural materials, waste solidification and durable buildings. It shows excellent potential. However, the compressive properties of geopolymers are still affected by the characteristics of their raw materials and preparation process, and improving their compressive strength is still an important research direction.
[0003] The existing methods for improving the compressive properties of geopolymers mainly include adjusting preparation conditions, mechanochemical treatment, composite silicon-aluminum-calcium materials, fiber reinforcement, organic modification, and microbial induced calcium carbonate precipitation (MICP). Methods for adjusting preparation conditions include, for example, optimizing the concentration of the stimulator, increasing the curing temperature, etc., mechanochemical treatment methods include, for example, reducing the particle size, increasing the specific surface area and reaction activity by ball milling, etc., methods for composite silicon-aluminum-calcium materials include, for example, supplementing active elements to form a dense three-dimensional network structure, adding calcium oxide or silica fume, fiber reinforcement methods include, for example, adding natural or synthetic fibers to inhibit crack propagation, such as polyvinyl alcohol fibers and steel fibers can improve bending strength and toughness, and organic modification methods include, for example, adding polyethylene glycol, epoxy resin, etc. to promote reaction rate and form a dense network structure. Although these traditional methods can improve the compressive properties to a certain extent, there are many problems and disadvantages. On the one hand, they generally have the problems of low efficiency, high cost, and complex operation, and it is often difficult to achieve efficient improvement of compressive properties while ensuring low cost. In addition, microbial induced calcium carbonate precipitation (MICP) has attracted attention as a new technology, but it also has its own shortcomings. MICP requires the cultivation of specific microorganisms and has strict requirements on the culture environment, including the precise control of temperature, pH value, nutrient concentration and other conditions, which makes the culture process complicated and prone to failure. Moreover, the entire reaction cycle of MICP is relatively long. It takes a lot of time from microbial cultivation to the induction of calcium carbonate precipitation, resulting in low efficiency. In addition, the steps are cumbersome, involving multiple links such as microbial cultivation, urease induction, and calcium carbonate precipitation control. Problems in any link may affect the final effect. Therefore, it is necessary to further develop new green, environmentally friendly and efficient technologies to change the compressive properties of geopolymers. Summary of the invention
[0004] The object of the present invention is to at least partially overcome the defects of the prior art and provide a method for increasing the compressive properties of geopolymers based on urease-induced calcium carbonate precipitation.
[0005] The present invention also aims to provide a method for increasing the compressive properties of geopolymers based on urease-induced calcium carbonate precipitation, which is simple to operate and low in cost.
[0006] The present invention also aims to provide a method for increasing the compressive properties of geopolymers based on urease-induced calcium carbonate precipitation, which has high environmental friendliness and resource utilization efficiency.
[0007] To achieve the above purpose or one of the purposes, the technical solution of the present invention is as follows:
[0008] A method for increasing the compressive properties of geopolymers based on urease-induced calcium carbonate precipitation, the method comprising:
[0009] Step S1: preparing a urease solution;
[0010] Step S2: preparing a cementing liquid;
[0011] Step S3: preparing fly ash-based polymer;
[0012] Step S4: curing the fly ash-based polymer at room temperature.
[0013] According to a preferred embodiment of the present invention, step S1 comprises:
[0014] Weighing a predetermined weight of soybeans and putting them into a grinder for grinding, and sieving the ground soybean powder to obtain soybean powder with uniform particle size;
[0015] Soybean powder and deionized water are mixed in a predetermined mass-volume ratio and stirred using a magnetic stirrer. The mixture is allowed to stand for 2-3 hours after stirring to allow the soybean powder to precipitate and the urease to be released into the upper solution.
[0016] The supernatant after standing was poured into a centrifuge tube and centrifuged at 3000 r / min and 4°C for 15 minutes to remove suspended impurities and obtain the supernatant, which was the urease extract.
[0017] According to a preferred embodiment of the present invention, the urease extract is stored in an environment of 4° C. to avoid the risk of enzyme inactivation caused by temperature fluctuations.
[0018] According to a preferred embodiment of the present invention, step S2 comprises:
[0019] Weigh a certain amount of urea, dissolve it in deionized water, and stir until it is completely dissolved;
[0020] Weigh calcium chloride and dissolve it in deionized water to form a 1 mol / L calcium chloride solution;
[0021] The urea solution and the calcium chloride solution were mixed in a volume ratio of 1:1 to form a cementing solution.
[0022] According to a preferred embodiment of the present invention, step S3 comprises:
[0023] Weigh fly ash and water glass, wherein the modulus of water glass is 1.4, and the ratio of water glass to fly ash is 0.7, pre-mix the water glass and fly ash in a stirrer, and stir to make the water glass and fly ash uniformly mixed;
[0024] Add the prepared cementing liquid and urease solution in sequence, stirring continuously to obtain a uniform slurry;
[0025] Pour the slurry into the mold and tap the bottom of the mold to remove any air bubbles.
[0026] According to a preferred embodiment of the present invention, in step S3, multiple groups of slurry samples are prepared, each group of slurry samples includes three samples, and the urease concentrations of the multiple groups of slurry samples are different.
[0027] According to a preferred embodiment of the present invention, step S4 comprises:
[0028] The fly ash-based polymer is sealed and stored in a 40°C oven for a 24h preliminary thermal curing process, and then demoulding is performed to obtain the fly ash-based polymer. The demoulded fly ash-based polymer is packaged in a sealed bag to ensure isolation from the external environment, and then placed in a room temperature environment for further curing treatment.
[0029] According to a preferred embodiment of the present invention, different curing times are set for different fly ash-based polymer samples, including at least 7 days, 14 days and 28 days, so as to evaluate and test their mechanical properties in different time periods.
[0030] According to a preferred embodiment of the present invention, the method further comprises:
[0031] Step S5: Conducting a compressive performance test on the fly ash-based polymer.
[0032] According to a preferred embodiment of the present invention, the compressive performance test of the fly ash-based polymer is carried out using an electro-hydraulic servo universal testing machine. Before the test, the cured samples are taken out of the sealed bags, and the samples are placed in the testing machine one by one. Pressure is slowly applied at a preset loading speed, and the sample's destructive stress and maximum bearing capacity are recorded.
[0033] According to a preferred embodiment of the present invention, the method further comprises:
[0034] Step S6: Conduct characterization tests on fly ash-based polymers.
[0035] According to a preferred embodiment of the present invention, Fourier transform infrared spectroscopy and scanning electron microscopy are used to characterize the cured samples, including: first, Fourier transform infrared spectroscopy test is performed, the cured samples are ground into powder and the spectrum is measured to confirm the calcium carbonate generated by the urease induced reaction and the bonding between it and the geopolymer matrix; then, the microscopic morphology and pore filling of the sample are observed using a scanning electron microscope to confirm the distribution effect of the calcium carbonate precipitation.
[0036] Compared with the prior art, the invention has the following beneficial effects:
[0037] (1) The compressive properties of fly ash-based polymers are improved by urease-induced calcium carbonate precipitation technology, which does not require cumbersome and complicated pre-treatment steps and is easy to operate. Compared with traditional reinforcement methods, this technology is more efficient and convenient. This technology has a wide range of applicability and can significantly enhance the mechanical strength of materials and is suitable for a variety of environmental conditions.
[0038] (2) The urease-induced calcium carbonate precipitation technology is used to deposit calcium carbonate in geopolymers, which not only enhances the compressive strength of the material, but also realizes the recycling of waste resources (such as fly ash), with low energy consumption, low carbon dioxide emissions, and no secondary waste, which meets the requirements of green environmental protection.
[0039] (3) In terms of process flow, the invention optimizes the reaction conditions of urease-induced calcium carbonate precipitation by rationally mixing urease, urea and calcium source, so that the generated calcium carbonate precipitate forms a stable composite structure with the geopolymer matrix, thereby improving the compressive resistance and achieving effective filling of the material pores.
[0040] (4) Compared with the traditional reinforcement technology that requires high temperature treatment, the present invention adopts a room temperature curing process, which not only reduces the damage to the geopolymer matrix structure, but also reduces energy consumption, so that it can be stably implemented under various environmental conditions.
[0041] In summary, this invention demonstrates outstanding advantages in environmental protection, high efficiency, durability and cost control, and provides innovative solutions for sustainable building materials and recycling of waste resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 A flow chart of a method for increasing the compressive properties of geopolymers based on urease-induced calcium carbonate precipitation according to an embodiment of the present invention;
[0043] Figure 2 The compressive strength results of fly ash-based polymers at different curing times are shown;
[0044] Figure 3 Fourier transform infrared spectra of fly ash-based polymer at different urease concentrations are shown;
[0045] Figure 4 This is a scanning electron microscope image of fly ash-based polymer;
[0046] Figure 5 An image showing a portion of a fly ash-based polymer prepared according to an example of the present invention. DETAILED DESCRIPTION
[0047] Exemplary embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the same or similar reference numerals represent the same or similar elements. In addition, in the detailed description below, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the disclosed embodiments. However, it is apparent that one or more embodiments may also be implemented without these specific details. In other cases, known structures and devices are embodied in a schematic manner to simplify the accompanying drawings.
[0048] The present invention relates to a method for changing the compressive properties of geopolymers based on urease-induced calcium carbonate precipitation technology. The method introduces calcium carbonate precipitation generated by urease-induced cementing fluid into fly ash-based polymers to optimize the pore structure of the material, thereby significantly improving the compressive properties and durability. The technology is particularly suitable for geopolymer materials that need to improve strength and durability, and is a green, environmentally friendly, low-cost innovative method for enhancing the compressive properties of geopolymers.
[0049] Specifically, the present invention aims to develop an efficient, green and sustainable technology for improving the compressive properties of fly ash-based polymers. In view of the difficulties faced by microbial induced calcium carbonate precipitation (MICP) technology, such as harsh microbial culture conditions, long growth and reproduction cycles, cumbersome process steps, and the need for fine control of inoculation, culture and reaction parameters, the present invention uses urease-induced calcium carbonate precipitation technology to induce the formation of calcium carbonate crystals in an alkaline environment through the catalytic action of urease, without the need to culture microorganisms, and then precipitate inside the matrix to improve the strength of the material. Geopolymer is an amorphous aluminosilicate inorganic polymer formed by alkali-activated Si and Al materials, and its three-dimensional network structure mainly depends on the alternating links of SiO4 and AlO4 tetrahedral chains. Through the combination of urease, calcium chloride and urea solution, the urease-induced calcium carbonate precipitation process can form dense calcium carbonate precipitation in the geopolymer matrix, fill the internal pores of the material, and thus improve its compressive properties. In the implementation process of the present invention, the reaction conditions of urease-induced calcium carbonate precipitation are optimized, so that the generated calcium carbonate precipitation is closely combined with the geopolymer structure, and the mechanical properties of fly ash-based polymers are significantly improved. Compared with the traditional compression strengthening method, the present invention is simple to operate, has low material cost, utilizes biological urease to produce calcium carbonate, has high environmental friendliness and resource utilization efficiency, and has good application prospects.
[0050] Urease-induced calcium carbonate precipitation is a process in which urease directly catalyzes the hydrolysis of urea to generate ammonium ions (NH4 + ) and carbonate ions (CO3 2- ), soluble calcium ions (Ca 2+ ) in the presence of urease, a reaction occurs to produce calcium carbonate precipitation. Urease-induced calcium carbonate precipitation is a precipitation technique based on biochemical reactions. The chemical reactions involved in the process are shown in (1.1)-(1.6):
[0051]
[0052]
[0053] Urease-induced calcium carbonate precipitation does not require microbial participation during the entire reaction process, does not involve biosafety risks and complex processes such as microbial culture, activation, and metabolic rate, and is therefore suitable for substrates with fine particle sizes; secondly, urease has an extremely small size and can achieve the filling of tiny pores; thirdly, the remaining urease can be naturally degraded, and the whole process is green and environmentally friendly. Among them, urease is the key to urease-induced calcium carbonate precipitation technology. In previous studies, commercial purified urease was used more frequently, which is expensive and cannot be widely used in real engineering. The inventors found that urease used for urease-induced calcium carbonate precipitation can be extracted from plants and bacteria. Studies have found that beans (such as soybeans, sword beans) and melons (watermelon seeds) are rich in urease, and plant urease is convenient and economical. Urease-induced calcium carbonate precipitation technology has the characteristics of mild reaction conditions and environmentally friendly operation process. The generated calcium carbonate precipitate can be deposited in the pores of geopolymers to fill and enhance, thereby improving the compressive properties of the material.
[0054] In the present invention, fly ash is used as the matrix material of the geopolymer, and a three-dimensional network structure containing Si and Al tetrahedral networks is formed through the excitation of an alkaline activator. Since there are many pores in the fly ash-based polymer, calcium carbonate precipitates can be generated in these pores and fixed in the matrix, thereby enhancing the density and strength of the structure. Compared with traditional reinforcement methods, urease-induced calcium carbonate precipitation technology uses calcium carbonate generated by biocatalytic reactions to directly fill the material, which can better combine with the matrix material, so that the calcium carbonate precipitate forms a stable composite structure with the geopolymer matrix, thereby improving the compressive properties of the material. In addition, by regulating the ratio of urease, urea and calcium source, the precipitation amount and distribution can also be optimized, thereby achieving the effect of further enhancing the mechanical properties of the material. The specific technical methods of the present invention are as follows:
[0055] (1) Experimental preparation for urease-induced calcium carbonate precipitation
[0056] Urease, which has high efficiency and specific catalytic effect, is an important component of urease-induced calcium carbonate precipitation technology. In this study, low-cost soybeans were selected as the extraction source of urease. After crushing and grinding, the supernatant was obtained by centrifugation to obtain the urease extract. To ensure the activity of urease, it was stored in an environment of 4°C. The binder is mainly composed of urea and a calcium source (such as calcium chloride, calcium nitrate, calcium acetate, etc.). Calcium chloride is selected in the specific embodiment of the present invention. The concentration and ratio of the binder are one of the factors affecting urease-induced calcium carbonate precipitation. The present invention selects a two-phase injection method, that is, the binder and the urease solution are injected into the sample successively, so that the urease-induced calcium carbonate precipitation can fully react inside the geopolymer.
[0057] (2) Preparation process of fly ash-based polymer
[0058] The selection of raw materials plays a decisive role in the preparation process of geopolymer materials and their final properties. In this experimental study, fly ash industrial waste was used as raw material, as well as chemical reagents such as water glass and sodium hydroxide. These raw materials play different roles in the synthesis process of geopolymers: fly ash, as a source of silicon and aluminum, provides the silicate and aluminate components required for the formation of geopolymers; water glass, as an alkaline activator, can promote the hydrolysis and polymerization of the active components of silicate; sodium hydroxide is used to adjust the modulus of water glass. The modulus of the activator refers to the molar ratio of SiO2 contained in the activator to the equivalent alkaline oxide Na2O. The ratio of water glass to fly ash is the liquid-to-solid ratio (L / S), which affects the mechanical properties of the geopolymer. After a large number of experimental optimizations, the present invention selects a water glass modulus of 1.4 and a liquid-to-solid ratio of 0.7, and the geopolymer has good mechanical properties. According to the preset experimental proportion, an electronic balance was used to weigh the corresponding materials, and urease solution, binder, and alkaline activator were prepared in turn. The mixture was fully mixed with the fly ash raw material and then transferred to a blender for stirring for 10 minutes. After that, the mixture was poured into a mold to obtain a fly ash-based polymer sample based on urease-induced calcium carbonate precipitation and a blank control group.
[0059] (3) Fly ash-based polymer curing at room temperature
[0060] Considering that high-temperature curing will destroy the particle structure of geopolymers, causing rapid dehydration and excessive shrinkage of geopolymers, the geopolymers were sealed and stored in a 40°C oven for 24 hours of preliminary thermal curing. Then, the fly ash-based polymer samples were demoulded and immediately packaged in sealed bags to ensure that they were isolated from the external environment. They were then placed in a room temperature environment for further curing treatment. The specific curing time was 7 days, 14 days, and 28 days, so as to comprehensively evaluate and test their mechanical properties at different time periods.
[0061] (4) Testing and characterization of geopolymer compressive properties
[0062] The mechanical properties of fly ash-based polymer samples cured for 7, 14, and 28 days at room temperature were tested, and an electro-hydraulic servo universal testing machine was used for data acquisition. The compressive strength at different curing periods was tested to evaluate the effect of urease-induced calcium carbonate precipitation technology on the compressive properties of fly ash-based polymers. The present invention uses a Fourier transform infrared spectroscopy scanning electron microscope to characterize the geopolymer samples and observe the internal structural characteristics of the samples and the degree of urease-induced calcium carbonate precipitation reaction.
[0063] Taking the change of the compressive properties of fly ash-based polymer by urease-induced calcium carbonate precipitation as an example, more specific experimental steps are described:
[0064] S1: Preparation of urease solution
[0065] 50g of soybeans were weighed using an electronic balance and then put into a grinder to be crushed into powder to ensure the uniformity of the powder to improve the efficiency of urease extraction. Subsequently, the crushed soybean powder was screened through a 100-mesh steel sieve to obtain soybean powder with uniform particle size. A certain amount of soybean powder and deionized water were weighed according to the experimental requirements, mixed at a mass volume ratio of 1:10, and stirred with a magnetic stirrer for 30 minutes to ensure that the urease in the soybean powder was fully dissolved and evenly distributed in the solution. After stirring, it was allowed to stand for 2-3 hours to allow the soybean powder to precipitate and the urease was fully released into the upper solution. The upper clear liquid after standing was carefully poured into a centrifuge tube, centrifuged at 3000r / min and 4°C for 15 minutes, and suspended impurities were removed by centrifugation to obtain a supernatant, which was a urease extract. In order to maintain the catalytic activity of urease, the extract should be stored in a 4°C environment to avoid the risk of enzyme inactivation caused by temperature fluctuations. The embodiment of the present invention selects urease concentrations of 10g / L and 1g / L.
[0066] S2: Preparation of cementing fluid
[0067] The preparation of the cementing fluid includes urea and calcium chloride. The concentration and ratio of urea and calcium chloride are important factors affecting the effect of urease-induced calcium carbonate precipitation reaction. Through experiments, we found that the concentrations of urea and calcium chloride were set to 1 mol / L, which can not only generate sufficient calcium carbonate precipitation, but also will not inhibit the catalytic activity of urease. First, weigh a certain amount of urea and dissolve it in deionized water, stirring until completely dissolved to ensure the uniformity of the solution; then, weigh calcium chloride and dissolve it in deionized water to form a 1 mol / L calcium chloride solution. Then, the urea solution and the calcium chloride solution are mixed in a volume ratio of 1:1 to form a cementing fluid. During the mixing process, it should be added slowly and stirred slightly to ensure that the resulting mixed solution is uniform and transparent so that it can fully react during subsequent use.
[0068] S3: Preparation of fly ash base polymer
[0069] The preparation of fly ash-based polymers has high requirements on the selection and proportion of raw materials. The fly ash used in the present invention provides a silicon and aluminum source for the geopolymer, while water glass (sodium silicate) acts as an alkali activator, which can promote the hydrolysis and polymerization of the active components of the aluminosilicate in the fly ash. During the preparation process, an electronic balance is first used to weigh the fly ash and water glass, wherein the water glass modulus is 1.4 and the liquid-solid ratio is 0.7, to ensure that the material has good mechanical properties after molding. The weighed water glass and fly ash are pre-mixed in a stirrer and stirred at a low speed for 5 minutes to evenly mix the water glass and fly ash. 2.5 ml of the prepared binder and 2.5 ml of urease solution are added to each sample in turn. The entire stirring process needs to last for 10 minutes to obtain a uniform slurry. The slurry is then poured into a mold with a size of 40×40×40 mm 3 , tap the bottom of the mold to remove bubbles and improve the compactness of the sample. In this experiment, there were experimental groups with urease concentrations of 1g / L and 10g / L, and a blank control group, with 3 samples in each group, and a total of 9 groups of samples were prepared.
[0070] S4: Curing of geopolymer at room temperature
[0071] In the initial curing stage of the fly ash-based polymer sample after molding, in order to avoid high temperature damaging the structure of the geopolymer, a 24-hour heat curing process was selected in a 40°C oven. This step can ensure the stability and hardness of the material structure in the initial stage. After the heat curing is completed, the sample is carefully removed from the mold and sealed in a sealed bag to avoid the influence of external humidity and temperature fluctuations, while maintaining the stability of the reaction during the curing process. The sealed samples are placed at room temperature for long-term curing, and taken out for compressive performance testing after a curing period of 7 days, 14 days, and 28 days.
[0072] S5: Geopolymer compression performance test
[0073] The compressive performance test of geopolymer samples was carried out using an electro-hydraulic servo universal testing machine. Before the test, the cured samples were taken out of the sealed bags, and the samples were placed in the testing machine one by one. Pressure was slowly applied at a loading speed suitable for the sample size, and the sample's failure stress and maximum bearing capacity were recorded. The compressive strength test was performed on each group of samples cured for 7 days, 14 days, and 28 days. The compressive strength data of each group of samples were recorded separately, and the effects of urease concentration, curing cycle and other parameters on the compressive performance of geopolymers were compared and analyzed to determine the actual effect of urease-induced calcium carbonate precipitation technology in improving the compressive performance of fly ash-based polymers.
[0074] S6: Geopolymer Characterization Tests
[0075] In order to deeply analyze the effect of urease-induced calcium carbonate precipitation on the microstructure of fly ash-based polymer, the present invention uses Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) to characterize the cured samples. First, the FTIR test is performed to measure the spectrum after the sample is ground into powder to confirm the calcium carbonate generated by the urease-induced reaction and its bonding with the geopolymer matrix. The micromorphology and pore filling of the sample are observed using SEM to confirm the distribution effect of calcium carbonate precipitation.
[0076] The reagent urea came from China National Pharmaceutical Group Chemical Reagent Co., Ltd.; the reagent calcium chloride came from Hunan Beekman Holdings Co., Ltd., China; the alkaline activator was industrial water glass and sodium hydroxide, which came from Henan Borun Casting Materials Co., Ltd. and Shanghai Aladdin Biochemical Technology Co., Ltd., China, respectively; the mixer model was NJ-160B, from Shangyu Binxin Instrument Factory, Shaoxing; the electronic balance came from Shanghai Yaoxin Electronic Technology Co., Ltd.; the electro-hydraulic servo universal testing machine came from Meters & Schwarz, USA; the Fourier transform infrared spectrometer model was Bruker VERTEX 70V, from Billerica, USA; the scanning electron microscope model was FEI Nova Nano SEM450, from Hillsboro, USA.
[0077] The compressive strength results of fly ash-based polymer obtained by the present invention under different curing times are as follows: Figure 2 As shown. The present invention utilizes urease-induced calcium carbonate precipitation technology to significantly improve the compressive properties of fly ash-based polymers, showing excellent engineering application prospects. Experimental data show that with the increase of the curing period, the degree of urease-induced calcium carbonate precipitation reaction gradually increases, and the compressive strength of the experimental group with urease added is significantly higher than that of the blank control group at 14 days and 28 days. Among them, group C with a urease concentration of 1g / L reached 93.468MPa in a 28-day curing period, while the blank control group was only 78.306MPa, indicating that an appropriate concentration of urease can effectively promote the formation of calcium carbonate precipitation and significantly improve the density and compressive strength of the material. At the same time, the experiment also found that with the increase of curing time, the precipitation of calcium carbonate is further stabilized and strengthened, and the mechanical properties of the material are gradually improved.
[0078] Fourier infrared spectra show the internal chemical structure of fly ash-based polymer after 28 days of curing. A is the blank control group, B is urease 10g / L, and C is urease 1g / L. At 3500cm -1 The obvious bands appearing near are related to the stretching vibrations of OH and NH in the sample. Since sodium silicate is used as an alkaline activator, products containing hydroxyl groups (-OH) will be generated during the reaction. At the same time, urease and urea are added to groups B and C, and the amino groups (-NH2) in urease and urea will also produce absorption peaks in this area. 1656cm -1The peak at 1450 cm shows the bending vibration of HOH, which is the bound water present in the geopolymer. -1 This region is usually related to C=O (carbonyl) stretching vibration, NH bending vibration, etc. A-28 has a relatively weak absorption peak in this region. B-28 and C-28 have stronger absorption peaks in this region because the added urease and urea participate in the reaction to generate compounds containing carbonyl or amino groups. 1016cm -1 The characteristic peak in the wave number region is a typical vibration signal of the Si-OT bond formed by silicon oxygen and another element T (possibly silicon or aluminum) in the three-dimensional network structure of the geopolymer, which is a significant indicator of the silicate glass phase. -1 This region is usually related to the stretching vibration of Si-O-Si (silicon oxide silicon) and Si-O-Al (silicon oxide aluminum). Since the fly ash-based polymer contains aluminosilicate structure and sodium silicate is used as an activator, there will be obvious absorption peaks in this region.
[0079] The scanning electron microscope image shows the microstructure of fly ash-based polymer sample group B after curing for 28 days. The image shows the surface morphology of the material, showing the urease-induced calcium carbonate crystal formation and fly ash raw material particles. The energy spectrum analysis (EDS) spectrum on the left shows the distribution of different elements at point A. It can be seen that there are obvious peaks of calcium, oxygen, and carbon elements, which can prove that the crystals here are generated calcium carbonate. The spherical fly ash particles are tightly combined with the gel, and a transition layer is formed between the raw material and the matrix phase, which indicates that a polymerization reaction has occurred between them, forming a [-Al-O-Si-] chemical bond. The cracks in the image are mainly caused by the sample after the compressive strength test. Through these analyses, we can gain a deeper understanding of the microstructure and elemental composition of fly ash-based polymers.
[0080] Compared with the prior art, the invention has the following beneficial effects:
[0081] (1) The compressive properties of fly ash-based polymers are improved by urease-induced calcium carbonate precipitation technology, which does not require cumbersome and complicated pre-treatment steps and is easy to operate. Compared with traditional reinforcement methods, this technology is more efficient and convenient. This technology has a wide range of applicability and can significantly enhance the mechanical strength of materials and is suitable for a variety of environmental conditions.
[0082] (2) The urease-induced calcium carbonate precipitation technology is used to deposit calcium carbonate in geopolymers, which not only enhances the compressive strength of the material, but also realizes the recycling of waste resources (such as fly ash), with low energy consumption, low carbon dioxide emissions, and no secondary waste, which meets the requirements of green environmental protection.
[0083] (3) In terms of process flow, the invention optimizes the reaction conditions of urease-induced calcium carbonate precipitation by rationally mixing urease, urea and calcium source, so that the generated calcium carbonate precipitate forms a stable composite structure with the geopolymer matrix, thereby improving the compressive resistance and achieving effective filling of the material pores.
[0084] (4) Compared with the traditional reinforcement technology that requires high temperature treatment, the present invention adopts a room temperature curing process, which not only reduces the damage to the geopolymer matrix structure, but also reduces energy consumption, so that it can be stably implemented under various environmental conditions.
[0085] In summary, this invention demonstrates outstanding advantages in environmental protection, high efficiency, durability and cost control, and provides innovative solutions for sustainable building materials and recycling of waste resources.
[0086] It should be noted that the present invention uses fly ash-based polymers to test and study the compressive properties, but there are a wide variety of geopolymers, including kaolin, blast furnace slag, rice husk ash, zeolite, clay, etc. The method of improving the compressive properties of geopolymers by urease-induced calcium carbonate precipitation is applicable to all geopolymers.
[0087] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that changes may be made to these embodiments without departing from the principles and spirit of the present invention. The scope of application of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for increasing the compressive properties of geopolymers based on urease-induced calcium carbonate precipitation, characterized in that: The method comprises: Step S1: preparing a urease solution; Step S2: preparing a cementing liquid; Step S3: preparing fly ash-based polymer; Step S4: curing the fly ash-based polymer at room temperature.
2. The method for increasing the compressive properties of geopolymers based on urease-induced calcium carbonate precipitation according to claim 1, characterized in that: The step S1 comprises: Weighing a predetermined weight of soybeans and putting them into a grinder for grinding, and sieving the ground soybean powder to obtain soybean powder with uniform particle size; Soybean powder and deionized water are mixed in a predetermined mass-volume ratio and stirred using a magnetic stirrer. The mixture is allowed to stand for 2-3 hours after stirring to allow the soybean powder to precipitate and the urease to be released into the upper solution. The supernatant after standing was poured into a centrifuge tube and centrifuged at 3000 r / min and 4°C for 15 minutes to remove suspended impurities and obtain the supernatant, which was the urease extract.
3. The method for increasing the compressive properties of geopolymers based on urease-induced calcium carbonate precipitation according to claim 2, characterized in that: The urease extract is stored in an environment of 4° C. to avoid the risk of enzyme inactivation caused by temperature fluctuations.
4. The method for increasing the compressive properties of geopolymers based on urease-induced calcium carbonate precipitation according to claim 3, characterized in that: The step S2 comprises: Weigh a certain amount of urea, dissolve it in deionized water, and stir until it is completely dissolved; Weigh calcium chloride and dissolve it in deionized water to form a 1 mol / L calcium chloride solution; The urea solution and the calcium chloride solution were mixed in a volume ratio of 1:1 to form a cementing solution.
5. The method for increasing the compressive properties of geopolymers based on urease-induced calcium carbonate precipitation according to claim 4, characterized in that: The step S3 comprises: Weigh fly ash and water glass, wherein the modulus of water glass is 1.4, and the ratio of water glass to fly ash is 0.7, pre-mix the water glass and fly ash in a stirrer, and stir to make the water glass and fly ash uniformly mixed; Add the prepared cementing liquid and urease solution in sequence, stirring continuously to obtain a uniform slurry; Pour the slurry into the mold and tap the bottom of the mold to remove any air bubbles.
6. The method for increasing the compressive properties of geopolymers based on urease-induced calcium carbonate precipitation according to claim 5, characterized in that: In step S3, multiple groups of slurry samples are prepared, each group of slurry samples includes three samples, and the urease concentrations of the multiple groups of slurry samples are different.
7. The method for increasing the compressive properties of geopolymers based on urease-induced calcium carbonate precipitation according to claim 6, characterized in that: The step S4 comprises: The fly ash-based polymer is sealed and stored in a 40°C oven for a 24h preliminary thermal curing process, and then demoulding is performed to obtain the fly ash-based polymer. The demoulded fly ash-based polymer is packaged in a sealed bag to ensure isolation from the external environment, and then placed in a room temperature environment for further curing treatment.
8. The method for increasing the compressive properties of geopolymers based on urease-induced calcium carbonate precipitation according to claim 7, characterized in that: Different curing times are set for different fly ash-based polymer samples, including at least 7 days, 14 days and 28 days, so as to evaluate and test their mechanical properties at different time periods.
9. The method for increasing the compressive properties of geopolymers based on urease-induced calcium carbonate precipitation according to claim 8, characterized in that: The method further comprises: Step S5: Conducting a compressive performance test on the fly ash-based polymer.
10. The method for increasing the compressive properties of geopolymers based on urease-induced calcium carbonate precipitation according to claim 9, characterized in that: The method further comprises: Step S6: Conduct characterization tests on fly ash-based polymers.
Citation Information
Patent Citations
Method for treating fly ash with microbes and method for producing building material from fly ash
CN106904854A
Method for inducing calcium carbonate precipitation by combining plant urease with urease inhibitor
CN114592498A
Method for synergistically solidifying tailing sand through EICP-casein
CN116573893A
Curing agent as well as preparation method and application thereof
CN117003533A
Fly ash-slag based geopolymer cementing material and preparation method thereof
CN118955027A
Cited By
A design method of urease-induced calcium carbonate precipitation solidification soil
CN122548851A
A design method of urease-induced calcium carbonate precipitation solidification soil
CN122548851B